2021
DOI: 10.1007/s12094-021-02573-1
|View full text |Cite
|
Sign up to set email alerts
|

SEOM clinical guidelines for pancreatic and biliary tract cancer (2020)

Abstract: Pancreatic cancer (PC) and biliary tract cancer (BTC) are both aggressive and highly fatal malignancies. Nowadays we have a profound knowledge about the molecular landscape of these neoplasms and this has allowed new therapeutic options. Surgery is the only potentially curative therapy in both cancers, but disease recurrence is frequent. In PC, adjuvant treatment with mFOLFIRINOX has improved overall survival (OS) and in BTC adjuvant treatment with capecitabine seems to improve OS and relapse-free survival. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Pancreatic cancer is one of the most common clinical tumors [31]. Early diagnosis is difficult, and comprehensive treatment based on surgery does not improve the survival time and quality of life of patients after surgery [32]. This study found that in human pancreatic cancer tissues, hsa_circ_0074298 comprised 1,486 bp and was produced by splicing parts of exons of the HARS gene.…”
Section: Discussionmentioning
confidence: 97%
“…Pancreatic cancer is one of the most common clinical tumors [31]. Early diagnosis is difficult, and comprehensive treatment based on surgery does not improve the survival time and quality of life of patients after surgery [32]. This study found that in human pancreatic cancer tissues, hsa_circ_0074298 comprised 1,486 bp and was produced by splicing parts of exons of the HARS gene.…”
Section: Discussionmentioning
confidence: 97%
“…These highly selected patients often benefit from surgical treatment. A unified standard of the indications for surgical treatment of multifocal iCCA is lacking among other guidelines [ 11 , 17 , 18 , 19 , 20 , 21 ]. As a result, the surgical treatment rate of T2mN0M0 is much lower than that of T2sN0M0.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most guidelines for GBC have recommended routine follow-up with a 3-month interval during the first 2 years after curative-intent therapy, and a 6-month interval thereafter, up to 5 years. 25 , 26 However, there is no research supporting a specific surveillance schedule for patients with GBC nor has there been any study focusing on the impact of regular follow-up on prognosis. The present study demonstrated that more than 80% of recurrence occurred within 29 months after resection (early recurrence), typically in a location distant from the primary tumor site.…”
Section: Discussionmentioning
confidence: 99%